Frequency of left ventricular systolic dysfunction in patients receiving Primary Percutaneous intervention vs Delayed Percutaneous intervention presenting with ST- Elevation Myocardial infarction - Yousuf, Muhammad Hannan; Majeed, Uzma; Basharat, Rida; Shahzad, Shahzaib; Awais, Muhammad Arsalaan; Mahboob, Hafiz Mudabbar (Biological and Clinical Sciences Research Journal, 2025)
Left ventricular systolic dysfunction (LVSD) is a significant complication following ST-elevation myocardial infarction (STEMI), associated with an increased risk of heart failure and long-term cardiovascular mortality. Primary percutaneous coronary intervention (PPCI) is the gold-standard treatment for STEMI, yet delayed PCI remains common in Pakistan due to limited healthcare accessibility and delayed patient presentation. This study compares the frequency of LVSD in STEMI patients undergoing PPCI versus delayed PCI at a tertiary care hospital in Lahore, Pakistan. Objective: To evaluate and compare LV systolic function in STEMI patients who underwent early PPCI versus delayed PCI, determining the impact of PCI timing on left ventricular ejection fraction (LVEF) and overall cardiac function. Methods: A prospective observational study was conducted at the Cardiology Department, Punjab Institute of Cardiology Lahore. One hundred sixty patients were enrolled and stratified into PPCI (n=80) and delayed PCI (n=80). Baseline demographics, comorbidities (hypertension, diabetes, dyslipidemia, smoking), and echocardiographic findings (LVEF, LVSD) were recorded. LVSD was defined as LVEF <40% at hospital discharge. Data were analysed using SPSS version 26, with chi-square and independent t-tests for statistical comparisons, considering p ≤ 0.05 statistically significant. Results: The overall prevalence of LVSD was 43.1%, with a significantly higher incidence in delayed PCI patients (57.5%) compared to PPCI patients (28.7%) (p < 0.001). Patients in the PPCI group had significantly higher LVEF at discharge (50.3% ± 7.2) compared to the delayed PCI group (42.1% ± 6.8, p < 0.05). Dyslipidemia (p = 0.001) was significantly associated with LVSD, whereas diabetes mellitus showed a borderline association (p = 0.06). Other risk factors, including hypertension and smoking, were not statistically significant predictors of LVSD. Conclusion: Early PCI significantly reduces the incidence of LV systolic dysfunction in STEMI patients, reinforcing the importance of timely reperfusion therapy to prevent long-term myocardial damage. Delays in PCI were associated with larger infarct size, lower LVEF, and a higher prevalence of LV dysfunction. Given the high burden of STEMI and PCI delays in Pakistan, healthcare policies should prioritise expanding PPCI-capable centres, improving emergency medical services (EMS), and raising awareness of early STEMI symptoms to enhance patient outcomes.